2016
DOI: 10.1097/mbc.0000000000000462
|View full text |Cite
|
Sign up to set email alerts
|

Increased fibrin formation and impaired fibrinolytic capacity in severe chronic kidney disease

Abstract: Chronic kidney disease (CKD) is associated with a concurrent increased risk of thrombosis and bleeding. We aimed to investigate whether CKD is associated with increased fibrin formation, impaired fibrin degradation, or both. Twenty-one patients with CKD stage 4 (CKD 4), 15 haemodialysis patients, and 13 controls (C) without kidney disease were studied. We used a global assay to determine fibrin formation and degradation in plasma. Fibrin turbidity was measured over time to obtain a value of the coagulation act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…Excessive fibrinolytic activity due to chronic hemodialysis resulted in increasing levels of FDP, D-dimer and hypofibrinogenemia. 1,16,17,21 According to Malyszko et al, and Mortberg, et al, in their research found high concentrations of fibrinogen, D-dimer, thrombin -antithrombin complex, factor VII, vWF, thrombomodulin, and PAI-1 in plasma of ESRD patients. 15 Research on FDP as a marker of fibrinolytic activity in various clinical manifestations is still rare.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Excessive fibrinolytic activity due to chronic hemodialysis resulted in increasing levels of FDP, D-dimer and hypofibrinogenemia. 1,16,17,21 According to Malyszko et al, and Mortberg, et al, in their research found high concentrations of fibrinogen, D-dimer, thrombin -antithrombin complex, factor VII, vWF, thrombomodulin, and PAI-1 in plasma of ESRD patients. 15 Research on FDP as a marker of fibrinolytic activity in various clinical manifestations is still rare.…”
Section: Resultsmentioning
confidence: 97%
“…15 Research on FDP as a marker of fibrinolytic activity in various clinical manifestations is still rare. 2,16 Hyperactive platelets caused by hemodialysis can lead to bleeding and thrombosis thus increasing morbidity and mortality. Prevention of hemostasis disorders is expected to extend the life of people with ESRD, so the presence of hypercoagulable markers of thrombosis in patients with uremia is warranted.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hui and Yu also alluded that our study did not explore the functions of the whole set of serum coagulant components on AKI from a “broader view, other than focusing on the single variable of platelet count.” Again, in support of their statement, they reference two studies conducted in nonsurgical populations- one on increased fibrin formation and impaired fibrinolysis capacity in severe chronic kidney disease, 10 and the other, on the role of tissue factor and coagulation factor VII levels in patients with acute myocardial infarction. 11 We are not aware of any studies to date to indicate that increased fibrin formation, impaired fibrinolysis capacity, tissue factor or coagulation factor VII levels play a significant role in the development of postoperative AKI after cardiac surgery.…”
mentioning
confidence: 97%